Terminally ill patients' and their relatives' experiences and behaviors regarding complementary and alternative medicine utilization in hospice palliative inpatient care units: a cross-sectional, multicenter survey - Yu-Jia Lin; Hsiao-Ting Chang; Ming-Hwai Lin; Ru-Yih Chen; Ping-Jen Chen; Wen-Yuan Lin; Jyh-Gang Hsieh; Ying-Wei Wang; Chung-Chieh Hu; Yi-Sheng Liou; Tai-Yuan Chiu; Chun-Yi Tu; et al. (BMC, 2023)
Abstract Background Terminally ill patients often experience exacerbations of diseases that render mainstream medicine ineffective in relieving symptoms, prompting attempts at complementary and alternative medicine (CAM). This study collected data from terminally ill patients and their relatives to determine differences between CAM use, behavioral patterns, and perceptions of health information about CAM. Methods A cross-sectional design using a self-administered questionnaire was adopted. Eight medical institutions in Taiwan with inpatient hospice palliative care units were chosen. Ninety-two terminally ill patients and 267 relatives met the inclusion criteria. The questions concerned the experience of CAM use, the kinds of products/services CAM provided, the purpose of CAM use, the source of CAM information, and the perceptions and attitudes toward CAM. Results Both terminally ill patients and their relatives have a high proportion of lifetime and one-year prevalence of CAM use (88.0% vs. 88.4%; p = 0.929). CAM use for musculoskeletal and neurological discomfort is higher among terminally ill patients than among their relatives. Relatives/friends are the most frequent sources of information on CAM (53.3% vs. 62.2%; p = 0.133). The percentage of terminally ill patients who discontinued mainstream medical treatment because of CAM use was higher than that of their relatives (18.5% vs. 9.3%; p = 0.026). More than half the terminally ill patients and their relatives had never been asked about CAM by medical staff (64.1% vs. 66.7%), nor had they informed medical professionals about the use of CAM products and services (63% vs. 66.9%). Random inquiries by medical professionals may be associated with increased disclosure of CAM use (terminally ill patients: odds ratio, 9.75; 95% confidence interval, 1.97-48.35 vs. relatives: odds ratio, 5.61; 95% confidence interval, 2.66-11.83). Conclusions The high prevalence and concealment of CAM use in terminally ill patients should be considered. Medical professionals should establish a friendly and barrier-free communication model, encourage patients to share CAM experiences, and provide evidence-based information on the use of CAM products and services, to reduce the potential damage caused by harmful use.